2005
DOI: 10.1177/030089160509100212
|View full text |Cite
|
Sign up to set email alerts
|

What is the Optimal Number of Lymph Nodes to be Dissected in Colorectal Cancer Surgery?

Abstract: Background Regional lymph node (LN) involvement in colorectal cancer (CRC) identifies the stage and the subset of patients who would benefit from adjuvant chemotherapy. We performed a retrospective analysis to determine if the number of recovered LNs was associated with long-term outcome in patients operated on for stage II and III CRC. Patients and methods Hospital records of 179 patients with CRC followed in our unit from 1997 to April 2003 were reviewed. Results On average 11.68 ± 7.3 LNs were sampled per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For example, Chang et al evaluated the prognostic effect of lymph nodes examined with the cut-off of 7, 32 and Gumus et al separated the population with 9 lymph nodes examined. 36 Moreover, in our dataset, three-quarter patients had been evaluated for >12 lymph nodes, which was much higher than the proportion reported earlier, where a population-based study suggested that only 37% of colon cancer patients had adequate lymph node evaluation (at least 12 nodes examined), 27 indicating the increased retrieval of lymph nodes in recent years. Multivariate analysis confirmed the prognostic value of the number of lymph nodes retrieved ( Table 4 ), while the overall survival showed that stage III disease was associated with a slightly better survival than stage II disease; this might probably have been due to the fact that there were cases of death from other causes rather than CRC, since for the cancer-specific survival, stage III patients had significantly larger HR than the stage II group.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For example, Chang et al evaluated the prognostic effect of lymph nodes examined with the cut-off of 7, 32 and Gumus et al separated the population with 9 lymph nodes examined. 36 Moreover, in our dataset, three-quarter patients had been evaluated for >12 lymph nodes, which was much higher than the proportion reported earlier, where a population-based study suggested that only 37% of colon cancer patients had adequate lymph node evaluation (at least 12 nodes examined), 27 indicating the increased retrieval of lymph nodes in recent years. Multivariate analysis confirmed the prognostic value of the number of lymph nodes retrieved ( Table 4 ), while the overall survival showed that stage III disease was associated with a slightly better survival than stage II disease; this might probably have been due to the fact that there were cases of death from other causes rather than CRC, since for the cancer-specific survival, stage III patients had significantly larger HR than the stage II group.…”
Section: Discussionmentioning
confidence: 54%
“… 18 , 27 , 33 While for stage III diseases, our results showed more number of lymph nodes examined significantly increased the cancer-specific survival, but the other studies found this prognostic value only existed in node-positive group. 17 , 34 36 This might be caused by the different cut-offs of lymph nodes examined in previous studies. For example, Chang et al evaluated the prognostic effect of lymph nodes examined with the cut-off of 7, 32 and Gumus et al separated the population with 9 lymph nodes examined.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, a complete pathology report is the basis for optimal individual treatment and may thus improve survival. It has previously been reported that adequate lymph node recovery results in improved survival for colonic cancer stage II disease [8,9] and there are indications that this may be true for stage III disease also [13–15]. However, these studies also suggest that other factors than stage migration may explain the better survival.…”
Section: Discussionmentioning
confidence: 99%
“…In UK, the current guidelines set by The Royal College of Pathologists recommend that all available lymph nodes in the resection specimen should be identified and analysed, and that individual centres should achieve a mean lymph node retrieval of 12 nodes per specimen [2]. Authorities in other countries recommend values ranging from eight to 14 nodes as representative of an adequate sample [3–10], although some authors have suggested that there should be no fixed minimum and that all nodes should be examined [11–13]. These guidelines are based on available published research, examining the potential impact of an adequate lymphadenectomy on survival.…”
Section: Introductionmentioning
confidence: 99%